Immune signatures of the POLE mutation in endometrial carcinomas: a systematic study based on TCGA data and clinical cohort validation - Wang, Tieyan; Yu, Dan; Wang, Juanjuan; Zhu, Ningning; Tang, Xian-bin; Chen, Xiuwen; Su, Xiao-min; Huang, Yu-gang (Frontiers in Oncology, 2023)
Background: POLE is a critical biomarker for endometrial cancer (ECs) prognosis and therapeutic decision. However, the immune infiltration and immunotherapy-related gene expression in the tumor microenvironment (TME) of POLE-mutated ECs remain unresolved.The TCGA database was used to characterize the TME of POLE mutants, which primarily included immune cells and co-expression genes. We used immunohistochemistry (IHC) to determine immune cell abundance and PD-L1 expression in 104 EC tissues, including 11 POLE mutants and 93 wild-type.The bioinformatic study found significant differences in gene expression of the chemokine family, immune-cell markers, and lysozyme in POLE mutants, along with immune response activation. In POLE-mutated ECs, the abundance of CD4+T, CD8+T, M1 macrophages, and dendritic cells increased considerably. Furthermore, POLE mutations may enhance immune cell recruitment or activation and lymphocyte homing in ECs. POLE mutants also had increased expression of immunecheckpoint suppressor genes such as PD-L1, CTLA-4, TIM-3, and others. The tumor mutation burden (TMB) was higher in ECs with POLE mutation. In the validation cohort, we discovered that POLE mutations were related to the immune infiltration abundance of CD8+, CD4+, and Foxp3+ POLE mutation immune-signatures in ECs 2 cells and PD-L1 expression by IHC. The prognosis of TCGA-ECs showed that the survival time of the CD8, CD4, PD-L1, or Foxp3 over-expression subgroup of the POLE mutants was significantly prolonged compared to the down-regulation subgroup or the POLE wild-type.The infiltration abundance of CD8 + T, CD4 + T, Foxp3 + T cells, and the expression of PD-L1 harbor crucial value for the prognosis or individualized therapy of POLE-mutated ECs.